Dampak Psikologis Korban Tsunami dan Pentingnya Dukungan Sosial dalam Pemulihan - Nova Ramadhini Rifmi Hasibuan (Jurnal Wacana Sosial Nusantara, 2025)
Indonesia is a country with a high level of natural disaster vulnerability, especially tsunamis, which cause physical damage, material losses, and long-term psychological effects on victims. Psychological disorders such as post-traumatic stress disorder (PTSD), anxiety, and depression are commonly experienced by survivors, including vulnerable groups such as children and the elderly, and can even last for decades after the disaster. This paper aims to examine the psychological impact of the tsunami and highlight the importance of social support and psychological intervention in the rehabilitation of victims. A review of the literature shows that the prevalence of post-disaster anxiety and depression is quite high, and psychological symptoms often persist in the long term. Social support from family, friends, and the community has been shown to play an important role in strengthening survivors' mental resilience and accelerating recovery, while psychological interventions such as trauma healing, counseling, psychosocial therapy, and cognitive behavioral therapy (CBT) are effective in reducing symptoms of PTSD, anxiety, and depression. Therefore, synergy between social support and integrated psychological services is essential as a key strategy for post-disaster rehabilitation so that survivors can return to functioning optimally in social and productive life.